Design and application of a fixing plate for abdominal drainage tube (一种腹腔引流管固定板的设计与应用) - WANG Jun (王俊); ZHANG Shichen (张诗晨); CAI Yingxuan (蔡颖萱); QIAN Xiaoge (茜晓格); GAO Qian (高倩) (中西医结合护理)
The purpose of indwelling abdominal drainage tube after abdominal operation is to drain the blood and fluid accumulated in the abdominal cavity after the operation, and to observe the condition and detect the complications such as abdominal hemorrhage and postoperative anastomotic fistula as early as possible. Effective fixation of abdominal drainage tubes is essential to prevent infection and promote wound healing. This paper introduces the design and application of a utility model abdominal drainage tube fixing plate, which can effectively improve the fixing and drainage effect, reduce the work burden of medical staff and improve the work efficiency. (腹部手术后一般常规留置腹腔引流管, 用于引流出术后腹腔内积存的渗血、渗液, 同时有利于观察病情, 及早发现有无腹腔出血及术后吻合口瘘等并发症。腹腔引流管固定对于预防感染和促进伤口愈合至关重要。本研究介绍了一款实用新型腹腔引流管固定板的设计和使用方法, 其有效提高了固定和引流效果, 同时减轻了医护人员的工作负担, 提高了工作效率。)